The Influence of Learning Approach and Eye-Hand Coordination Against The Results of A Free Throw in Basketball Games - Wardana, Pramoda; Hidayatullah, M.Furqon; Kiyatno, Kiyatno (Department of Physical Education, Sport, Health and Recreation, 2017)
The purposes of this recearch were to examine the influence of direct and indirect learning approaches on free throw result in basketball, the difference of free throw result played by students with good and poor hand-eye coordinations, and the interaction influence of learning approach and hand-eye coordination on the result. This research applied experimental method with 2x2 factorial design. The population within this study was male students in 5th semester of the major program. Purposive Random Sampling was used as the sampling technique. 40 students were taken as the samples, in which students with good and poor hand-eye coordinations were equal. The analytical technique of this study belonged to ANOVA to use SPSS 22 and 5% significancy. Study result showed the difference of significant influence between direct and indirect learning approaches on free throw result, for p-value = 0,045, smaller than 0,05; the difference of increase in the result from students with good and poor hand-eye coordinations, for p-value = 0,035, smaller than 0,05; and the interaction of learning approach and hand-eye coordination on the result, for p-value = 0, 012, smaller than 0,05.It is concluded that there were differences of the significant influence between the learning approaches on free throw result, the free throw result from students with good and poor hand-eye coordinations, and there was an interaction influence of learning approaches and hand-eye coordination on the free throw result.